Contribution of Critical Reading Skills and Scientific Vocabulary Mastery to Exposition Text Writing Skills - Maharani Dwi Putri Asriati; Erizal Gani (STAI Hubbulwathan Duri, 2022)
The purpose of this study was to describe the contribution of critical reading skills to students' exposition text writing skills, to describe the contribution of scientific vocabulary mastery to students' exposition text writing skills, to describe the contribution of students' critical reading skills and scientific vocabulary mastery to students' exposition text writing skills. This type of research is quantitative with a descriptive method using a correlational design. The population of this research is the students of class X senior high school totalling 223 people. Sampling was carried out using proportional random sampling. The number of research samples was 45 students. The research instrument is an objective test and a performance test. The research data were in the form of exposition text writing skill scores, critical reading skills test scores, and students' scientific vocabulary mastery scores which were converted into grades. Data analysis used the Pearson product-moment correlation test, multiple correlation test, t-test, f-test, and determinant coefficient to determine the contribution of the independent and dependent variables. The results showed that critical reading skills contributed significantly 36.72% to the skill of writing exposition texts. Mastery of scientific vocabulary contributed significantly by 36.97% to the skill of writing expository text. Critical reading skills and scientific vocabulary mastery together contribute to the skill of writing expository text by 42.25%. In conclusion, critical reading skills and scientific vocabulary mastery together have a significant contribution to exposition text writing skills.